T cells from hemophilia A subjects recognize the same HLA-restricted FVIII epitope with a narrow TCR repertoire - Ettinger, Ruth A.; Paz, Pedro; James, Eddie A.; Gunasekera, Devi; Aswad, Fred; Thompson, Arthur R.; Matthews, Dana C.; Pratt, Kathleen P. (Blood, 2016)
Factor VIII (FVIII)–neutralizing antibodies (“inhibitors”) are a serious problem in hemophilia A (HA). The aim of this study was to characterize HLA-restricted T-cell responses from a severe HA subject with a persistent inhibitor and from 2 previously studied mild HA inhibitor subjects. Major histocompatibility complex II tetramers corresponding to both of the severe HA subject's HLA-DRA-DRB1 alleles were loaded with peptides spanning FVIII-A2, C1, and C2 domains. Interestingly, only 1 epitope was identified, in peptide FVIII2194-2213, and it was identical to the HLA-DRA*01-DRB1*01:01-restricted epitope recognized by the mild HA subjects. Multiple T-cell clones and polyclonal lines having different avidities for the peptide-loaded tetramer were isolated from all subjects. Only high- and medium-avidity T cells proliferated and secreted cytokines when stimulated with FVIII2194-2213. T-cell receptor β (TCRB) gene sequencing of 15 T-cell clones from the severe HA subject revealed that all high-avidity clones expressed the same TCRB gene. High-throughput immunosequencing of high-, medium-, and low-avidity cells sorted from a severe HA polyclonal line revealed that 94% of the high-avidity cells expressed the same TCRB gene as the high-avidity clones. TCRB sequencing of clones and lines from the mild HA subjects also identified a limited TCRB gene repertoire. These results suggest a limited number of epitopes in FVIII drive inhibitor responses and that the T-cell repertoires of FVIII-responsive T cells can be quite narrow. The limited diversity of both epitopes and TCRB gene usage suggests that targeting of specific epitopes and/or T-cell clones may be a promising approach to achieve tolerance to FVIII. •An HA subject with a multiexon F8 deletion showed a highly clonal response to 1 FVIII epitope via an immunodominant TCR.•The same HLA-DRA*01-DRB1*01:01-restricted FVIII epitope was recognized by T cells from 3 HA subjects.